Pengaruh Gadget Terhadap Ahklak Dan Moral Siswa Di Sekolah Dasar Negeri 47 Kota Ternate - Adam, Adiyana; Abdullah, Putri Widyasari; Diva, Famela; Hamid, Ismawati (Sekolah Tinggi Agama Islam Babussalam Sula, 2022)
The purpose of this study is to describe the use of gadgets and to find out the factors that influence the morals of the students of SDN 47 Ternate City. This study uses a qualitative approach with the research subject being the principal's class teacher and students. Data collection was carried out through observation, interviews and documentation. The data analysis technique used is data reduction, display, and conclusion drawing. Based on the results obtained, the bad influence of using gadgets on children's morals by students of SDN 47 Ternate City, namely students become lazy to study, lazy to do activities because they are focused on playing games on gadgets, sleeping too late at night when playing gadgets, there is no initiative to help parents and you have to be called first before you want to help and even then you are lazy and there are many reasons because you are too busy playing games. And the decline in the morale of SDN 47 Ternate City students is that students are addicted to playing games, the lack of attention from parents in accompanying children when playing gadgets. the use of gadgets on the formation of children's personality or character, among others, children will become more lazy, lack of self-confidence in children, reduced children's communication skills, children will be more introverted, children's dependence on playing gadgets, and the most dangerous negative impact is children can freely access sites on the internet that can damage children's morals. Factors causing changes in children's morale are influenced by the habits of school students in using gadgets to play online games compared to online learning.